2020
DOI: 10.3390/jcm10010083
|View full text |Cite
|
Sign up to set email alerts
|

Thromboembolic and Bleeding Risk in Atrial Fibrillation Patients with Chronic Kidney Disease: Role of Anticoagulation Therapy

Abstract: Atrial fibrillation (AF) and chronic kidney disease (CKD) are strictly related; several independent risk factors of AF are often frequent in CKD patients. AF prevalence is very common among these patients, ranging between 15% and 20% in advanced stages of CKD. Moreover, the results of several studies showed that AF patients with end stage renal disease (ESRD) have a higher mortality rate than patients with preserved renal function due to an increased incidence of stroke and an unpredicted elevated hemorrhagic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 136 publications
1
22
1
Order By: Relevance
“…This is contrary to other studies in which obesity paradox was observed, potentially because of differences in the adopted adjustment for risk factors [24,25]. The vital impact of impaired renal function, as an independent variable, on outcomes in AF, as in many other diseases, explains these findings [26][27][28][29][30].…”
Section: Discussioncontrasting
confidence: 64%
“…This is contrary to other studies in which obesity paradox was observed, potentially because of differences in the adopted adjustment for risk factors [24,25]. The vital impact of impaired renal function, as an independent variable, on outcomes in AF, as in many other diseases, explains these findings [26][27][28][29][30].…”
Section: Discussioncontrasting
confidence: 64%
“… 55 , 56 Given the remarkable safety profile of DOACs compared with VKAs, emerging evidence supports their use in high‐risk populations such as elderly, renal impairment, peripheral artery disease, and AF in the context of congenital heart disease and cardiomyopathies. 57 , 58 Similarly, several case reports have demonstrated that DOACs could be at least as effective and safe as warfarin in preventing cardioembolic events in NCCM patients. 59 , 60 Skidan et al .…”
Section: Stroke Prevention In Noncompaction Cardiomyopathymentioning
confidence: 99%
“…Well‐known therapeutic advantages of DOACs, including improved safety, reduced risk of bleeding, increased adherence to therapy, and convenience during long life oral therapy, could be preciously useful in young NCCM patients, especially in children. 54 , 58 , 64 The latter category is the most challenging one because no randomized trials on DOACs have been published for paediatric patients and VKAs still represent the first‐choice anticoagulation therapy. Unfortunately, VKAs have numerous drug interactions, as well as their efficacy can be influenced by the vitamin K intake from the diet.…”
Section: Stroke Prevention In Noncompaction Cardiomyopathymentioning
confidence: 99%
“…The ventricular myocardium involvement is associated with hampered left ventricle filling and diastolic stiffness [ 119 , 121 ], mainly determined by inflammation related titin phosphorylation [ 122 ]. The atrial myocardium involvement is associated with fibrosis and atrial fibrillation [ 119 , 123 , 124 , 125 , 126 ]. Inflammatory-metabolic HFpEF is typical phenotype of aged women with many cardiovascular comorbidities.…”
Section: The Pathophysiology Of Heart Failure With Preserved Ejection Fractionmentioning
confidence: 99%